Numerical Study on the Performance and NOx Emission Characteristics of an 800cc MPI Turbocharged SI Engine - Seungmin Kim (MDPI AG, 2021)
The main purpose of this study is to optimize engine performance and emission characteristics of off-road engines with retarded spark timing compared to MBT by repurposing the existing passenger engine. This study uses a one-dimensional (1D)-simulation to develop a non-road gasoline MPI turbo engine. The SI turbulent flame model of the GT-suite, an operational performance predictable program, presents turbocharger matching and optimal operation design points. To optimize the engine performance, the SI turbulent model uses three operation parameters: spark timing, intake valve overlap, and boost pressure. Spark timing determines the initial state of combustion and thermal efficiency, and is the main variable of the engine. The maximum brake torque (MBT) point can be identified for spark timing, and abnormal combustion phenomena, such as knocking, can be identified. Spark timing is related to engine performance, and emissions of exhaust pollutants are predictable. If the spark timing is set to variables, the engine performance and emissions can be confirmed and predicted. The intake valve overlap can predict the performance and exhaust gas by controlling the airflow and combustion chamber flow, and can control the performance of the engine by controlling the flow in the cylinder. In addition, a criterion can be set to consider the optimum operating point of the non-road vehicle while investigating the performance and exhaust gas emissions accompanying changes in boost pressure With these parameters, the design of experiment (DoE) of the 1D-simulation is performed, and the driving performance and knocking phenomenon for each RPM are predicted during the wide open throttle (WOT) of the gasoline MPI Turbo SI engine. The multi-objective Pareto technique is also used to optimize engine performance and exhaust gas emissions, and to present optimized design points for the target engine, the downsized gasoline MPI Turbo SI engine. The results of the Pareto optimal solution showed a maximum torque increase of 12.78% and a NOx decrease of 54.31%.